Noncoercive nonlinear Dirichlet problems in unbounded domains. (March 2020) - Alfano, Emilia Anna; Monsurrò, Sara
Abstract: In this paper we study noncoercive nonlinear Dirichlet problems with discontinuous coefficients in unbounded domains. An existence result is proved exploiting suitable coercive nonlinear approximate Dirichlet problems.